Padrão de ocupação de hábitat das espécies dominantes de characiformes do Lago Guaíba (Rio Grande do Sul, Brasil) em função de parâmetros ambientais naturais - Alves, Thais Paz (2015)
Guaíba Lake, one of five biologically defined units of the Patos Lagoon system, is extremely important for its rich biodiversity and the numerous habitats distributed along its length. Due to the increase in both urbanization and industry on the shores of this environment, the characterization of the current habitat status of this ecosystem is essential for the implementation of effective conservation measures. Fish have been previously studied as indicators of environmental quality. Consequently, several parameters were utilized to determine the spatial distribution factors of species of Characiformes, one of the most representative orders of South America. Over a two year period (from February 2012 to February 2014), 59 surveys were completed at different locations within Guaíba Lake - connection points with rivers, streams, margins and the pelagic region. At each point continuous and binary abiotic data (e.g. water parameters, characterization of sediment and landscape), were collected, in addition to biotic data (e.g. macroinvertebrate community composition). Ten species of Characiformes were identified from gillnets (mesh size 15-70 mm): Acestrorhynchus pantaneiro, Astyanax sp. aff. fasciatus, Astyanax jacuhiensis, Cyphocharax voga, Hoplias malabaricus, Leporinus obtusidens, Oligosarcus jenynsii, Oligosarcus robustus, Prochilodus lineatus and Schizodon jacuiensis. To quantify the influence of each variable in the distribution of fish population we generated Generalized Additive Models (GAM) in R Software. Due to the large number of descriptors, in this paper we present an unusual methodology, initially splitting all parameters into six functional groups (water, sediment 1 and 2, macroinvertebrates, macrohabitat and morphometric variables). Subsequently, we modelled the most important ones in two stages, leaving the most significant subset of descriptors that determine the distribution of each species. The distribution of the two most abundant species, A. sp. aff. fasciatus and C. voga, was determined by four distinct variables. The former, by riparian vegetation, Gastropoda, DO and margin; the latter, by particle size 0.25 and <0.63 mm, shoal and distance from the channel. O. jenynsii distribution was determined by one variable (temperature), O. robustus by seven variables (particle size 0.25 mm, Chironomidae, emergent, riparian and floating vegetation, pH and Patos), A. jacuhiensis by two variables (distance from the channel and stream), A. pantaneiro by three variables (average diameter of sediment particles, distance from the shore and Guaíba) and finally H. malabaricus by five variables (average diameter of sediment particles, distance from the channel, floating vegetation, vegetated margin and particle size <0.63 mm). Insufficient numbers of the three least abundant species, P. lineatus, L. obtusidens and S. jacuiensis, were collected for analysis.